A Decade of Ecosystem-Scale Research at an Aridland Constructed Treatment Wetland - Childers, Daniel L. (Frontiers in Environmental Science, 2020)
Cities are increasingly pursuing more resilient and sustainable futures. One way to do so is by the increased use of Urban Ecological Infrastructure (UEI), including constructed treatment wetlands (CTW). This strategy is particularly important for aridland cities with scarce water resources. In this paper I synthesize nearly ten years of systems-level research at the Tres Rios CTW in Phoenix, AZ USA. Since July 2011, a research team that includes dozens of student volunteers has been sampling monthly for herbaceous biomass and productivity, water quality, transpiration rates, and aquatic metabolism. We also quantify belowground biomass and plant tissue nutrient content annually, and measured greenhouse gas fluxes from 2012 - 2014. Our peak summer biomass values are among the highest reported in the literature, and high rates of transpiration are associated with this biomass. Using our whole-system water budgets and tracer studies we have documented a slow movement of surface water into the marsh from adjacent open water areas that is driven by transpirational losses and that we refer to as the “biological tide”. With our nitrogen (N) budgets for the whole system and the vegetated marsh we showed that roughly 50% of the annual N uptake by the vegetated marsh is driven by new water entering via this biological tide. Our aquatic metabolism sampling suggested that the N uptake associated with the autotrophic water column was roughly 27% of the average annual N uptake by the vegetated marsh. The marsh is a source of CH4 and N2O across the air-water interface and the plants are a net source of CH4 but a net sink for N2O. Our combined flux estimates suggest that the Tres Rios marshes are a net sink for greenhouse gas equivalents because of this plant-mediated net uptake of N2O. Finally, over the years our Tres Rios CTW project has provided a platform for dozens of students and young people to experience ecological research, both in the field and in the lab.